Die Matrikel der Universität Wien, VII Band 1715/16 bis 1745/46 VII. Band: 1715/16-1745/46 - Mühlberger, Kurt (2011)
The seventh volume of the Matriculation Book of the University of Vienna includes the period from 1715/16 to 1745/46. It represents the follow-up of the edition of the central student enrollments of the rectors of the University of Vienna, that was initially established in 1377. It is a first-class source for studies of the history of persons and the institution of the University of Vienna, as well as the social history of the scholarly world in the period of enlightenment. The register book includes informations about the scholarly staff and the students. Within 31 years there are 6.764 persons enrolled. In addition, the book contains information on the regional and social origins of university members. Apart from the critical edition of the matriculation text, the volume also includes a list of university rectors. Moreover it is accompanied by indices of persons and places.